Examining the Role of Oil and Non-Oil Revenues, and Oil Price Fluctuations on Economic Growth in African Oil Exporting Countries - Gaballa, Farag khalifa; Haron, Nazatul Faizah (International Journal of Digital Marketing Science, 2025)
This study investigates the complex relationships between oil revenues, non-oil revenues, oil price fluctuations, and economic growth in African oil-exporting countries. Targeting Nigeria, Angola, Algeria, Libya, and Egypt, the research analyzed a comprehensive dataset spanning 1970-2023 using advanced second-generation panel econometric techniques. The cross-sectional Autoregressive Distributed Lag (ARDL) model examined the long-run and short-run dynamics of economic growth determinants. The sample comprised five leading African oil-producing countries, with data sourced from the World Bank Development Database. Results demonstrated significant positive relationships between GDP and oil revenue, non-oil revenue, oil prices, capital, and labor. The research revealed the critical importance of economic diversification, human capital investment, and strategic revenue management in driving sustainable economic growth. The study offers substantial implications for policymakers, economists, and development practitioners by providing insights into economic transformation mechanisms in resource-dependent economies. It contributes to resource economics literature by offering empirical evidence of complex economic interactions in African contexts. The originality of the research lies in its comprehensive approach, innovative methodological techniques, and detailed exploration of economic growth dynamics in African oil-exporting countries.